Hybridization engineering of oxyfluoride aluminosilicate glass for construction of dual-phase optical ceramics - Du, Guanxin (2024)
The construction of transparent ceramics under mild conditionsand standard atmospheric pressure has great scientific and technological potential; however, it remains difficult to achieve when conventional ceramic sintering techniques are used. Herein, a mild strategy for constructing dual-phase optical ceramics with high crystallinity (>90%) based on the stepped dual-phase crystallization of hybridized aluminosilicate glass is presented. Theoretical and experimental studies reveal that the hybridization of the glass system enables a new balance between the glass-forming ability and crystallization and can overcome the uncontrolled devitrification phenomenon during the dense crystallization of glass. Transparent hybridized oxide-fluoride ceramics with fiber geometry and dual-phase microstructures are also successfully fabricated. The generality of the strategy is confirmed, and transparent ceramics with various chemical compositions and phase combinations are prepared. Additionally, the cross-section of the ceramic fibers can be easily tuned into a circle, square, trapezoid, or even a triangle. Furthermore, the practical applications of optical ceramics for lighting and X-ray imaging are demonstrated. The findings described here suggest a major step toward expanding the scope of optical ceramics.